Assessment of Knowledge about Radiation Hazards and Radiation Protection among Health Workers in Bharatpur Hospital, Nepal - Paudel, Keshab; Sapkota, Surya Prakash; Paudel, Samikshya; Mallik, Mukesh (Journal of Bharatpur Hospital, 2026)
Background Since ionising radiation is used for both diagnosis and treatment by radiology, orthopaedic surgeons, urologists, and others, hospital staff of different layers and different departments are regularly exposed to radiation. To keep the radiation level low and staff protected, it is necessary to have knowledge of radiation hazards and protection. Thus, this aims to assess knowledge of healthcare workers about radiation hazards and radiation protection. Methods Cross-section study conducted over 260 participants through structured questionnaire of 17 questions. Knowledge level was scored and then categorised as good and poor. Descriptive statistics was calculated and association was verified by Chi-Squared test and Fisher’s exact test. Results There were 57% staff who had good level of knowledge. There were 21.92% staff who were trained about radiation hazards and only 24.23% used TLD badge. Majority (40.38%) were exposed in fluoroscopy. There was association of predicting variables with outcome variable knowledge level. Conclusions Although the radiation at work place is sensitive issue, knowledge level is poor among many staff. Training should be provided not only to radiology staff but to staff of all the layers and all the departments who are exposed to radiation. They all should be registered for TLD badge as well.